Evaluasi Penerapan Pelayanan Konseling Berbasis Syariah terhadap Kepuasan Pasien di Puskesmas Srondol Semarang : Evaluation of the Implementation of Syariah-Based Counseling Services on Patient Satisfaction at the Srondol Semarang Community Health Center - Yuyun Darma Ayu Ningrum; Anik Moeljani; Desi Renianti (Indonesian Journal of Pharmacy and Natural Product, 2023)
Patient satisfaction is an assessment of the good and bad quality of health services received by patients. Patients will feel satisfied if the performance of the health services they receive is the same as or exceeds their expectations. The level of patient satisfaction is very important and is closely related to the level of patient return visits so that this can be used as an indicator of the quality of health services. This study aims to determine the application of sharia-based counseling services to patient satisfaction at the Srondol Semarang health center. The method used in this research is an observational method, carried out by collecting data on the research object by administering a questionnaire stating patient satisfaction with sharia-based counseling services for Srondol Health Center patients. The results of the validity test produce an r value for each statement > 0.361 (valid). The reliability test was carried out using the Cronbach Alpha test> 0.6 (reliable) for each questionnaire item. The results of testing using a questionnaire obtained an average result of 47.6% satisfied patients, 40.67% very satisfied and 11.67% dissatisfied with sharia-based counseling services at the Srondol Health Center. Evaluation of the implementation of sharia-based counseling services on patient satisfaction at the Srondol Semarang Community Health Center is based on Islamic law. ABSTRAK Kepuasan pasien merupakan penilaian terhadap baik buruknya kualitas pelayanan kesehatan yang diterima oleh pasien. Pasien akan merasa puas apabila kinerja pelayanan kesehatan yang diperoleh sama atau melebihi harapannya. Tingkat kepuasan pasien sangat penting dan berhubungan erat dengan tingkat kunjungan kembali pasien sehingga hal ini dapat digunakan sebagai indikator terhadap kualitas pelayanan kesehatan. Penelitian ini bertujuan untuk mengetahui penerapan pelayanan konseling berbasis syariah terhadap kepuasan pasien di puskesmas Srondol Semarang. Metode yang digunakan pada penelitian ini adalah metode observasional, dilakukan dengan pengumpulan data terhadap objek penelitian dengan cara memberikan kuesioner pernyataan kepuasan pasien terhadap pelayanan konseling berbasis syariah pasien Puskesmas Srondol. Hasil uji validitas menghasilkan nilai r untuk masing-masing pernyataan > 0,361 (valid). Tes reliabilitas dilakukan dengan menggunakan uji Cronbach Alpha >0,6 (reliabel) untuk masing-masing item kuesioner. Hasil pengujian menggunakan kuesioner didapatkan hasil rata-rata pasien merasa puas sebanyak 47,6%, sangat puas 40,67% dan tidak puas sebanyak 11,67% terhadap pelayanan konseling berbasis syariah di puskesmas srondol. Evaluasi penerapan pelayanan konseling berbasis syariah terhadap kepuasan pasien di Puskesmas Srondol Semarang telah dilandasi syariat islam.